A time series econometric analysis of the impact of domestic debt on national saving: evidence from sri lanka - Selvamalai, V.T. (University of Jaffna, 2016)
Domestic debt is a major source of public debt in Sri Lanka. Public debt, as well as domestic debt, has a crucial role in an economy where the saving is an element of the economy. Therefore, the study examines the effect of domestic debt on national saving, and also examines the causal relationship between these two variables in Sri Lanka over the period between 1977 and 2014. For the study, the data was gathered from Annual Report of Central Bank of Sri Lanka, 2014. The study applies times series econometric method. Especially distributed lag model and Granger Causality test was applied to this data. The study found that, in the short-run, the changes in domestic debt-to-GDP ratio have affected negatively and significantly on the change in national saving-to-GDP ratio in Sri Lanka between 1977 and 2014. But in the long-run, there is no statistical evidence to effect a change in domestic debt-to-GDP ratio in change of economic growth in Sri Lanka after 1977. Further, from the Granger causality test, the study found that there is no causal relationship between the domestic-to-GDP ratio and national saving-to-GDP ratio in Sri Lanka between 1977 and 2014.
Keywords: Domestic debt; Effect and relationship; National saving